Extreme risk protection order use in six US states: a descriptive study - Leslie M. Barnard; Marian E. Betz; Shannon Frattaroli; Christopher E. Knoepke; Annette Christy; Julia P. Schleimer; Veronica A. Pear; Megan McCarthy; Reena Kapoor; Michael A. Norko; Ali Rowhani-Rahbar; Wenjuan Ma; et al. (Injury Epidemiology)
Abstract Objectives Extreme Risk Protection Orders (ERPOs) are civil court orders that temporarily prohibit firearm purchase and possession by someone (“respondent”) at imminent risk of harming themselves or others. Despite ERPOs being currently available in 21 states, DC, and U.S. V.I., little is known about the circumstances under which they are used across states. Methods Using a standardized protocol, we abstracted ERPO petitions and associated court documents from 6 states to examine characteristics of respondents, documented risks of harm, and court outcomes. Included cases were filed through June 30, 2020, from 2013 (Connecticut) or from when the law went into effect (California: 2016; Colorado: 2020; Florida: 2018; Maryland: 2018; and Washington: 2016). Results There were 6,634 ERPO petitions across included states. The median age of respondents was 40.0 years (SD: 16.4), and 10.8% were female. Almost half of petitions noted suicidal threats, plans, or ideation (43.9%) as the precipitating event, half noted interpersonal violence threats (50.8%), and one quarter (24.6%) noted threats to both self and others. Around one third (36.0%) noted unlawful or reckless firearm use. The majority of petitions (84.1%) indicated the respondent had current or recent access to a firearm. Most (77.5%) of the final orders (post-hearing) were granted. ERPO implementation varied across states, particularly with regard to how frequently they were used, for what type of threat, and by what type of petitioner. Conclusions This study examined ERPO law implementation in 6 states, highlighting differences and similarities. This comparison allows for a more nuanced understanding of variation in ERPO use, which can inform ERPO implementation and future studies of ERPOs’ effectiveness.